PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, PERTUMBUHAN ASET TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 - 2016 - Vega Rizkha Agnestiya, 13.05.52.0023; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the effect of profitability, liquidity, firm size, and asset growth on capital structure. This research was conducted at a manufacturing company in Indonesia Stock Exchange which go public. Sampling method using purposive sampling with research period 2014 until 2016. The data is processed as many as 232 companies. The technique of testing the data using multiple linear regression analysis. The results showed that profitability, firm size, asset growth did not affect the capital structure, while liquidity in this study had a negative effect on capital structure. Keywords: Profitability, Liquidity, Company Size, Asset Growth